Identifying NOx Sources in Arequipa, Peru Using Nitrogen Isotopes in Particulate Nitrate - Michalski, Greg; E. Larrea Valdivia, Adriana; Olson, Elizabeth; Welp, Lisa; Fang, Huan; Magara-Gomez, Kento; Morales Paredes, Lino; Reyes Larico, Juan; Li, Jianghanyang (Frontiers in Environmental Science, 2022)
We reported on the first time series of δ15N in aerosol nitrate from South America. Particulate matter less than 2.5 microns in diameter (PM2.5) was collected at four sites located in Arequipa, a major city in southern Peru. The δ 15N values for nitrate in PM2.5 ranged from -1.7–15.9‰ and averaged 5.3 ± 3.0‰, with no significant difference between the four study sites and no discernable seasonal trend. These values are significantly higher than those in aerosol nitrate from southern hemisphere marine environments and those from the northern hemisphere. We explain the elevated values using an isotope mass balance mixing model that estimates a source NOx δ15N of -8 ± 3‰, derived mainly from anthropogenic sources (vehicles, industry). An isotope enabled 0-D photochemical box model was used to estimate the isotope enrichment of nitrate relative to NOx due to kinetic, equilibrium, and photolysis isotope effects occurring during NOx oxidation. This “source plus photochemistry” approach resulted in general agreement with the observations. This suggests that if the photochemistry effect can be accounted for, nitrate δ15N can be used to assess the relative importance of NOx sources and could be a new tool to validate NOx emission inventories.